2008
DOI: 10.1107/s1600536808014785
|View full text |Cite
|
Sign up to set email alerts
|

Redetermination of tricalcium trilanthanum pentakis(orthoborate) from single-crystal data

Abstract: Single crystals of the title compound, Ca3La3(BO3)5, were obtained by spontaneous nucleation from a high-temperature melt. The crystal structure of Ca3La3(BO3)5 has been determined previously from X-ray powder data [Zhang, Liang, Chen, He & Xu (2001). J. Alloys Compd, 327, 96–99]. The present refinement shows a significant improvement in terms of the precision of the geometric parameters and the correct determination of the absolute configuration in space group P63 mc with all atoms refined with anisotropic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…In order to confirm the structure and evaluate the content of impurity phase, Rietveld structure refinements for Ca 3 La 3(1– x ) Ce 3 x (BO 3 ) 5 ( x = 0, 0.01, 0.04, 0.10, 0.30, and 0.50) compounds were performed using the powder diffraction data. The P 6 3 mc structure reported by Zhou et al was used as an initial model in the Rietveld analysis. The refined unit cell parameters and residual factors are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to confirm the structure and evaluate the content of impurity phase, Rietveld structure refinements for Ca 3 La 3(1– x ) Ce 3 x (BO 3 ) 5 ( x = 0, 0.01, 0.04, 0.10, 0.30, and 0.50) compounds were performed using the powder diffraction data. The P 6 3 mc structure reported by Zhou et al was used as an initial model in the Rietveld analysis. The refined unit cell parameters and residual factors are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…10 Zhang et al reported the red emission under UV excitation of Eu 3+ in Ca 3 La 3 (BO 3 ) 5 from a sol−gel process. 11 The structure of Ca 3 La 3 (BO 3 ) 5 was first solved by Zhang 12 from the powder XRD data and then confirmed by Zhou 13 using the singlecrystal X-ray diffraction data. The structure consists of isolated triangle BO 3 groups with large cations La 3+ and Ca 2+ located in 10-coordinate and 8-coordinate environments, respectively, which are able to accommodate the lanthanide elements and thus may serve as a host for two-center luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the decay time of 4 F 3/2 to 4 I 11/2 transition in NAB is about 20 ms, which is much shorter than that of a commercial Nd:YAG laser (230 ms), and it is still difficult to grow NAB crystals with sufficient size and high optical quality, 10 thus it is very necessary to explore new selfactivated materials, especially with a high activator content. Two series of rare earth borates, Ca 3 La 3 (BO 3 ) 11,12 and Cd 4 ReO(BO 3 ) 3 (Re = Y, Gd, Lu), 13 were previously reported. Based on the structures of the compounds, the concentrations of the rare earth elements can be calculated to be about 1 Â 10 22 ions per cm 3 for Ca 3 La 3 (BO 3 ) and about 4.5 Â 10 21 ions per cm 3 for Cd 4 ReO(BO 3 ) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The crystal structure of the HL Ca 3 La 3 (BO 3 ) 5 (CLBO) has been determined previously. 8,9 The structure consists of isolated BO 3 triangles and a distorted [ CaO 8 ] and [LaO 10 ] polyhedral, which are able to accommodate the luminescent ions, and thus may serve as a HL for two-center luminescence (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%